2016
DOI: 10.1007/s10561-016-9595-0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering for neurodegenerative diseases using human amniotic membrane and umbilical cord

Abstract: Regenerative medicine, based on the use of stem cells, scaffolds and growth factors, has the potential to be a good approach for restoring damaged tissues of the central nervous system. This study investigated the use of human amniotic mesenchymal stem cells (hAMSC), human amniotic epithelial stem cells (hAESC), and human Wharton's jelly mesenchymal stem cells (hWJMSC) derived from human umbilical cord as a source of stem cells, and the potential of the human amniotic membrane (HAM) as a scaffold and/or source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…hADSCs showed significant osteogenic phenotypes in previous study (Zuk et al, 2002 ), and our data further demonstrated that hADSCs exhibited higher osteogenic differentiation compared with hEnSCs and hDPSCs. Additionally, hDPSCs showed more remarkable osteogenic potential compared with hEnSCs as well, which was consistent with the previous publication (Tabatabaei and Torshabi, 2017 ).…”
Section: Resultssupporting
confidence: 92%
“…hADSCs showed significant osteogenic phenotypes in previous study (Zuk et al, 2002 ), and our data further demonstrated that hADSCs exhibited higher osteogenic differentiation compared with hEnSCs and hDPSCs. Additionally, hDPSCs showed more remarkable osteogenic potential compared with hEnSCs as well, which was consistent with the previous publication (Tabatabaei and Torshabi, 2017 ).…”
Section: Resultssupporting
confidence: 92%
“…Some placenta-derived products are already used for tissue regeneration [1,[3][4][5][6][7][8][9][10][11][12][13]. Nevertheless, when non-decellularized, they are only used in poorly vascularized sites, such as some wounds, tendon, ligament and cartilage [13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, bacterial debris and cellular components remaining inside the graft after sterilization may have a detrimental effect on osseointegration process [ 12 , 13 ]. Lomas et al [ 14 ] previously described a wash protocol for the recovered donor bone which since then has been optimized for better removal of protein, fat, blood and bone marrow [ 15 , 16 ]. Current scientific data on the biological performance of washed and γ-irradiated bone allografts as scaffolds for MSCs in comparison to other processing methods is limited.…”
Section: Introductionmentioning
confidence: 99%